The Influence Of Ad Types And Advertising Platforms On Marketing Effectiveness - R. Satria Setyanugraha Setyanugraha; Desti Ambarwati Ambarwati; Ridha Nurshofa Maulana Maulana; Rieliphia Meilinda Meilinda; Septiani Putri Putri; Zakaria Agusman Agusman (ICON Publisher, 2025)
This study aims to evaluate and analyze the Influence of Advertising Types and Advertising Platforms on Marketing Effectiveness. In addition, this study also aims to identify whether there is a direct influence between advertising platforms on marketing effectiveness and how the combination of advertising types and advertising platforms can affect overall marketing effectiveness. This study was conducted empirically in Purwakarta Regency to provide specific insights into the dynamics of digital marketing in the Purwakarta Regency area. Data were taken from online questionnaires to respondents, namely MSME actors in Purwakarta Regency. This study uses a quantitative study design with an empirical approach to evaluate the influence of Advertising Types and Advertising Platforms on Marketing Effectiveness in Purwakarta Regency. This study found that advertising types have a significant influence on advertising platforms, indicating that companies should start using higher advertising platforms that tend to be more active in marketing campaigns. This study focuses on two factors that drive marketing effectiveness for MSME actors in Purwakarta Regency. This study integrates empirical analysis in Purwakarta Regency to evaluate the Influence of Advertising Types and Advertising Platforms on Marketing Effectiveness.